2023
DOI: 10.1101/2023.01.05.22283441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Use of cytokine-induced killer cell therapy in colorectal cancer patients: a systematic review and meta-analysis

Abstract: Background: The number of clinical studies evaluating the benefit of cytokine-induced killer cell (CIK) therapy, an adoptive immunotherapy, for colorectal cancer (CRC) are increasing. In many of these trials CIK therapy was co-administered with conventional cancer therapy. The aim of this review is to systematically assess the available literature, in which the majority were only in Chinese, on CIK therapy for the management of CRC using meta-analysis, and to identify parameters associated with successful CIK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…We recently reported that past clinical studies on CIK cell therapy for CRC were generated from autologous patient-derived PBMCs [ 11 ]. Thus, we investigated if PBMCs from CRLM donors have similar capacity to produce CIK cells as healthy donors.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported that past clinical studies on CIK cell therapy for CRC were generated from autologous patient-derived PBMCs [ 11 ]. Thus, we investigated if PBMCs from CRLM donors have similar capacity to produce CIK cells as healthy donors.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in four studies reporting CIK cell therapy for CRLM each used a different production protocol [ 14 , 28 , 37 , 38 ]. Media used included serum free media or media supplemented with human serum or FBS ([ 11 ] and unpublished observations). While FBS supplementation is still common practice in cell culture for T cell therapies [ 39 ], its use increases the risk of xenoimmunisation and zoonotic disease transfer in recipients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Media usage ranged from SFMs to serum supplemented media including the use of human serum and FBS ( [11] and unpublished observations). While FBS supplementation is still common practice in cell culture for T cell therapies [39], its use increases the risk of xenoimmunisation and zoonotic disease transfer in recipients [16].…”
Section: Discussionmentioning
confidence: 99%